Analysis of Fatty Acids and Amino Acids of Three Local Freshwater Bagridae Fish Species in the Kampar Kanan River, Indonesia, for Food Security - Azrita Azrita; Hafrijal Syandri; HazlinaAhamad Zakeri; Harfiandri Damanhuri; Netti Aryani (International Journal of Food Science)
Fish have become an irreplaceable dietary source of animal protein, especially among households with low socioeconomic status in rural and urban areas of Indonesia. This study is aimed at analysing the proximate composition, minerals, fatty acids, and amino acids of three local Bagridae fish species in the Kampar Kanan river, Indonesia. The standard AOAC method was employed to examine the proximate composition of the carcass, and the analysis of amino acids and fatty acids was conducted through HPLC and GC-MS, respectively. The mineral content was determined using AAS. The nutrient composition results of Hemibagrus nemurus, Hemibagrus wyckii, and Mystus nigriceps revealed that the protein content was 24.26%, 22.57%, and 21.39% (% dry weight), whereas the total lipid content was 6.64%, 7.47%, and 7.75%, respectively. Regarding mineral contents, the calcium levels ranged from 1.49 to 1.66 mg/g, iron levels from 28.35 to 40.36 μg/g, and zinc levels from 24.03 to 54.46 μg/g. Among the fatty acids, palmitic acid was the most abundant in all three species, accounting for 25.59–30.70% of the total fatty acids. Additionally, significant amounts of C18:1 (oleic acid), C18:0 (stearic acid), and C20:4 (arachidonic acid) were also detected as primary fatty acids. The calculated atherogenic index values in the three species of Bagridae fish ranged from 0.73 to 0.99, while the thrombogenic index values varied between 0.54 and 0.75. The predominant amino acids found in the three species of Bagridae fish were glutamic acid with their concentrations ranging from 9.10 to 24.34%. These results indicate that consuming the meat of these three freshwater Bagridae fish species caught in the wild does not pose any health risks to consumers. They can be considered a safe and suitable food source with good nutritional quality.